Panicocene Narrazioni su cambiamenti climatici, regimi di mobilità e migrazioni ambientali - Giacomelli, Elena (Consumo, Comunicazione, Innovazione, 2023)
In a context of growing concern about the impacts of climate change and increasing alarmism toward migration phenomena, the possibility of "environmental migration" attracts considerable attention. What are the (in)desired effects of such an encounter? This volume sets out to decolonize the imaginary, seeking to deconstruct privilege (primarily that of the researcher), and use intersectional, decolonial, and feminist lenses to decentralize the image and construct new paradigms about narratives about the nexus between climate change and migration. The goal is to accompany readers to a new concept, that of Panicocene, the age of panic, a time when the two phenomena that characterize the contemporary meet in a unique narrative, an emergency squared that causes stasis and ineptitude. Panicocene thus encapsulates both the state of the art of research conducted in recent years and the starting point for future research. Panicocene, in fact, is also the title of the Marie Curie Global Fellowship project, which investigates the narratives and imaginaries of the nexus between the climate crisis and mobilities, to which the book provides an initial critical reflection.